Health Risk Assessment in Forensic and Mortuary Services at Persahabatan General Hospital: Identifying and Mitigating Occupational Hazards - Ratman, Muhammad Faisal; Meilia, Putri Dianita Ika; Ariningsih, Ariningsih; Mubin, Ma’rifatul (Universitas Muhammadiyah Yogyakarta, 2025)
Forensic and mortuary personnel face significant occupational hazards, yet comprehensive health risk assessments in these settings remain limited. This study assessed workplace risks at the Forensic Medicine and Mortuary Unit of Persahabatan General Hospital using the Health Risk Assessment (HRA) framework to recommend effective control measures. Seventeen personnel participated, with data collected through interviews, questionnaires, walk-through surveys, and internal records. Environmental measurements included noise levels (sound level meters), lighting (lux meters), and air quality parameters such as PM2.5, PM10, formaldehyde, and total volatile organic compounds (TVOCs). Ergonomic risks were assessed using REBA and ROSA, while psychosocial risks were analyzed using the SV-NBJSQ. The key risks identified were low back pain, nasopharyngeal carcinoma, leukemia, computer vision syndrome, and irritant contact dermatitis. Contributing factors included manual handling, awkward postures, insufficient lighting, and exposure to formalin. Proposed solutions encompassed introducing ergonomic tools, implementing educational programs, and revising operational guidelines. These interventions aim to reduce workplace hazards, enhance worker safety, and improve overall productivity. This study provides a structured approach for implementing workplace safety interventions, offering a model that can be applied in forensic and mortuary settings globally.